Optimum curvature in pit slope design - Dhar B.B.; Shrivastva B.K.; Raj G. (My University, 2025)
In surface mining the curvature of the pit slope is an important parameter in its safe and economic design. Research has shown that concave slope faces are more stable than planar or convex ones. The object of this paper is to demomstrate the effect of concavity on the optimum curvature, for the two slope angles commonly practiced in surface mines, 60° and 65°. The Finite Element Method (FEM) was used to simulate the variable mining conditions and the changing material properties. The analysis has been limited to stress analysis and the corresponding factor of safety to arrfve at on optimum slope curvature. © 1987, Taylor & Francis Group, LLC. All rights reserved.